You Better Go See Geri : An Odawa Elder's Life of Recovery and Resilience - Roossien, Geri, 1932-2019; Riley-Mukavetz, Andrea (Book collections on Project MUSE., 2021)
"Born into an Odawa family in Michigan in 1932, Frances "Geri" Roossien lived a life that was both ordinary and instructive. As a child, she attended Holy Childhood Boarding School; as an adult, she coped with her trauma through substance abuse; and in recovery she became a respected elder who developed tribally centered programs for addiction and family health, including the first Native American Recovery Group. While a graduate student, Andrea Riley Mukavetz was invited into Geri's home to listen to her stories and assist in compiling and publishing a memoir. Geri wanted her stories to serve as a resource, form of support, and affirmation that Indigenous people can be proud of who they are and overcome trauma. Geri hoped to be a model to current and future generations, and she believed strongly that more Indigenous people should become substance abuse counselors and work with their communities in tribally specific ways. Geri died in 2019, but Riley Mukavetz carried on the work. This book presents Geri's stories, lightly edited and organized for clarity, with an introduction by Riley Mukavetz that centers Geri's life and the process of oral history in historical and theoretical context"--